MEMBACA ULANG TEKS AL-QURAN DALAM PERSPEKTIF FEMINISME SERTA PENGARUHNYA TERHADAP AKSES KEADILAN SOSIAL DI INDONESIA - andrisari, dian (State of Islamic Institute Langsa, 2019)
This article examines the influence of feminist discourse through the contextual approach of the holy book (Qur'an) and its influence on access to social justice. The main argument of this article states the contextualization of feminist discourse in Islam by re-reading the verses of the Qur?an which leds misogynistic in practice experiencing complexity and difficult paths. Using a feminine perspective, this article traces the interpretation of the Qur'anic text and the hadiths are detrimental to women. Therefore,